Treating donor cells with 2-PCPA corrects aberrant histone H3K4 dimethylation and improves cloned goat embryo development. (4th May 2018) - Mao, Tingchao; Han, Chengquan; Deng, Ruizhi; Wei, Biao; Meng, Peng; Luo, Yan; Zhang, Yong
ABSTRACT: Epigenetic modifications extensively occur in mammalian embryonic development and cell differentiation process. They play an essential role in the reprogramming of nuclei during somatic cell nuclear transfer (SCNT) and subsequent in vitro embryonic development. Recently, SCNT embryos have been verified to contain a subnormal level of histone H3K4 dimethylation (H3K4me2) in contrast to in vitro fertilized embryos. This finding suggested that increasing H3K4me2 levels may ameliorate the aberrant development of cloned embryos. In this study, we investigated the influence of treating donor cells with trans-2-Phenylcyclopropylamine (2-PCPA), a specific inhibitor of lysine-specific demethylase 1 (LSD1), on embryogenesis, H3K4me2 level, and gene expression in cloned goat embryos. Treated goat fetal fibroblast cells (GFFs) with 2-PCPA served as donor cells for subsequent SCNT. Results showed that H3K4me2 levels in treated GFFs increased gradually with the increasing 2-PCPA concentration ( p < 0.05) and had no obvious influence in cell viability. The 2-PCPA-induced up-regulation of H3K4me2 levels led to G0/G1 cell cycle arrest and the difference was significant at 2μM compared with the control group ( p < 0.05). Interestingly, the development rate of goat SCNT embryos in vitro was significantly improved and aberrant H3K4me2 levels were effectively corrected in 2-PCPA-treated SCNT embryos in contrast to that in SCNT control embryos. Moreover, 2-PCPA treatment promoted the mRNA expression of key developmental genes Oct4 and Sox2 ( p < 0.05) without affecting the expression levels of imprinted genes IGF2R and H19 in goat SCNT embryos. These results indicated that abnormal H3K4me2 status can be corrected and SCNT embryo development can be promoted through treatment of donor cells with 2-PCPA. Abbreviations: SCNT: somatic cell nuclear transfer; H3K4me2: H3K4 dimethylation; 2-PCPA: trans-2-Phenylcyclopropylamine; LSD1: lysine-specific demethylase 1; GFFs: goat fetal fibroblast cells; IVF: in vitro fertilization; iPS: induced pluripotent stem; PBS: phosphate-buffered saline; IVM: in vitro maturation; RNAPII: RNA polymerase II; HMTs: histone methyltransferase